Development of an In Situ Cancer Vaccine via Combinational Radiation and Bacterial‐Membrane‐Coated Nanoparticles. Issue 43 (16th September 2019) - Patel, Ravi B.; Ye, Mingzhou; Carlson, Peter M.; Jaquish, Abigail; Zangl, Luke; Ma, Ben; Wang, Yuyuan; Arthur, Ian; Xie, Ruosen; Brown, Ryan J.; Wang, Xing; Sriramaneni, Raghava; et al.
Abstract: Neoantigens induced by random mutations and specific to an individual's cancer are the most important tumor antigens recognized by T cells. Among immunologically "cold" tumors, limited recognition of tumor neoantigens results in the absence of a de novo antitumor immune response. These "cold" tumors present a clinical challenge as they are poorly responsive to most immunotherapies, including immune checkpoint inhibitors (ICIs). Radiation therapy (RT) can enhance immune recognition of "cold" tumors, resulting in a more diversified antitumor T‐cell response, yet RT alone rarely results in a systemic antitumor immune response. Therefore, a multifunctional bacterial membrane‐coated nanoparticle (BNP) composed of an immune activating PC7A/CpG polyplex core coated with bacterial membrane and imide groups to enhance antigen retrieval is developed. This BNP can capture cancer neoantigens following RT, enhance their uptake in dendritic cells (DCs), and facilitate their cross presentation to stimulate an antitumor T‐cell response. In mice bearing syngeneic melanoma or neuroblastoma, treatment with BNP+RT results in activation of DCs and effector T cells, marked tumor regression, and tumor‐specific antitumor immune memory. This BNP facilitates in situ immune recognition of a radiated tumor, enabling a novel personalized approach to cancer immunotherapy using off‐the‐shelf therapeutics. Abstract : Tumor‐directed radiation therapy can result in immunogenic cell death and neoantigen release, yet on its own, it rarely induces a long‐term antitumor immune response. Therefore, a bacterial membrane nanoparticle is designed to bridge innate and adaptive immune activation after radiation therapy and results in improved tumor responses in immunologically "cold" tumors.